Precision laser manufacturing and metrology of nature-inspired bioactive surfaces for antibacterial medical implants - Hawi, Sara; Goel, Saurav; Kumar, Vinod; Giusca, Claudiu; Pearce, Oliver; Ayre, Wayne Nishio (Elsevier, 2025)
Femtosecond laser ablation presents a highly promising method to create bioactive nano/micro-structured metallic surfaces, offering numerous avenues for fabricating diverse types of surface structures. However, the relationship between surface properties and biological functionality, leading to the observed bioactivity remains unclear. This study aimed to investigate the relationship between structured/patterned steel surfaces and bioactivity, identifying key factors that enhance their performance. As opposed to the commonly used controversial parameter, arithmetic surface roughness (Ra), fractal dimension analysis was discovered to be strongly representative in quantifiably evaluating the adhesion of Staphylococcus aureus NCTC 7791 and MG-63 osteoblast-like cells. Surface chemistry and surface energy of structured surfaces showed no significant influence on bacterial adhesion. A specific type of laser-induced periodic structured surfaces with sub-micron wavelengths, high fractal dimension, and high texture aspect ratio demonstrated a 63 % reduction in bacterial adhesion compared to flat surfaces while avoiding cytotoxicity to MG-63 cells. Our findings underline the importance of scale-dependent analysis and the use of fractal analysis in evaluating the effectiveness of laser-structured surfaces for orthopaedic implant applications.
Keywords: Laser ablation; Surface structuring; Bacterial adhesion; Fractal dimension; Orthopaedic implant; 4014 Manufacturing Engineering; 40 Engineering; 3406 Physical chemistry; 4016 Materials engineering